Identifying and understanding disease burden in patients with inflammatory bowel disease - Casper Steenholdt; Lars Erik Kristensen; Mark Andrew Ainsworth; Tanja Schjødt Jørgensen; Jørn Brynskov; Katrine Risager Christensen; Marie Skougaard; Sine Buhl (BMJ Open Gastroenterology)
Objective Physicians tend to focus on biomedical targets while little is known about issues important to patients. We aimed to identify critical concepts impacting patients with inflammatory bowel disease (IBD).Design We performed a survey of patients with IBD in biologic therapy (n=172) and used a validated qualitative method called group concept mapping (GCM) in patient workshops. The survey included 13 questions on attitudes toward symptoms and issues related to IBD. In the eight workshops, patients (n=26) generated statements later clustered into concepts identifying issues impacting a patient’s life. Patients ranked the statements.Results In the survey, patients’ mean age were 40 years (SD 13), 53% were women, and 38% had ulcerative colitis. They identified fatigue (57%) and stool frequency (46%) as the most critical symptoms impacting their daily lives regardless of disease activity. In the GCM workshops with Crohn’s disease (n=13) (median age 42 years (IQR 39–51) and 62% were women), 335 statements divided among 10 concepts were generated, and the three most important concepts were ‘Positive attitudes’, ‘Accept and recognition’, and ‘Sharing knowledge and experiences in life with Crohn’s disease’. In the workshops with ulcerative colitis (n=13) (median age 43 years (IQR 36–49) and 69% were women), 408 statements divided into 11 concepts were generated; the most important concepts were ‘Take responsibility and control over your life’, ‘Medication’, and ‘Everyday life with ulcerative colitis’.Conclusion Focusing solely on IBD symptoms, patients identified fatigue and stool frequency to impact daily life the most. However, when investigating the disease burden in a broader perspective beyond classic IBD symptoms, patients identified concepts with focus on emotional health to be most important.Trial registration The Copenhagen University Hospital, Herlev and Gentofte approved the questionnaire and methodology (work-zone no: 18015429).